Eksploitasi Pekerja Anak Pemulung (Equilibrium: Jurnal Pendidikan, 2019)
This study aims to find out what is behind the exploitation of child labor and what are the steps of the government to minimize the exploitation of child labor in the city of Makassar, especially in the Manggala sub-district. The type of research used is descriptive qualitative research method by means of sampling through Purposive Sampling techniques by selecting a number of informants who have criteria that have been determined by researchers who know about the exploitation of child labor. The results of the study show that the background of the causes of exploitation of child labor in the city of Makassar is the factors of poverty and the influence of the social environment around it, and as for the steps taken by the government to minimize exploitation of child labor by opening free education around the area and by providing understanding to parents that the child should have an education not work. Keywords: Exploitation, Child Labor and Social Aberration